Education and Attitudes toward Interpersonal and State-Sanctioned Violence. Issue 3 (20th March 2018) - Schnabel, Landon
ABSTRACT: The link between education and liberal attitudes is among the most consistent findings in public-opinion research, but the theoretical explanations for this relationship warrant additional attention. Previous work suggested that the relationship is due to education socializing students to the "official culture" of the United States. This study uses the World Values Survey and General Social Survey to examine Americans' attitudes toward the justifiability of violence. I find that Americans with more education are less likely to say that interpersonal violence—against women, children, and other individuals—can be justifiable. However, they are more likely to say that state-sanctioned violence—war and police violence—can be justifiable. These patterns are consistent with a modified socialization model of education and social attitudes. I conclude that American education socializes people to establishment culture, identity, and interests, which differentiate between unacceptable interpersonal violence and ostensibly acceptable state-sanctioned violence.